An Analysis of Students’ Grammatical Errors in Arranging Jumbled Words into Meaningful Sentences of the Einght Grade at SMP Negeri 4 Banyuwangi in the Academic Year 2016/2017 - Pangestu, Dilla Ayuning (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2018)
Writing cannot be separated from sentences. Constructing sentences is astart to write a composition since it has levels of difficulties starting from wordsto sentences, sentences to paragraph and paragraph to longer composition.Jumbled words is a method of teaching. There are some words or sentenceswhich are jumbled by teacher and the students must arrange them intocorrect sentences. This research is a descriptive quantitative one that focusedon the data analysis with form description with the scoring of the eight gradestudents’ grammatical errors in arranging jumbled words into meaningfulsentences at SMP Negeri 4Banyuwangi in the Academic Year 2016/2017. Purposive method was used todetermine the research area. The number of respondent were 30 students.The result of the data analysis showed that compose sentences was difficultfor the eight year students of SMP Negeri 4 Banyuwangi. (1) There are 126miordering of using adjective followed by noun with the percentage 23,37%.(2) There are 46 misordering of using verb followed byadverb with the percentage 8,53%. (3) There are 98 misordering of usingauxiliary verb ( do, do es and did )with the percentage 18,18%, (4) There are 95 misordering of using to be pasttense (was and were) with the percentage 17,62%. (5) There are75misordering of using Simple Present Tense with the percentage 13,91%. (6)There are 99 misordering of using Simple Past Tense with the percentage18,36%